Ternary silicide formation from Ni-Pt, Ni-Pd and Pt-Pd alloys on Si(100): Nucleation and solid solubility of the monosilicides. (15th May 2017) - Schrauwen, A.; Demeulemeester, J.; Deduytsche, D.; Devulder, W.; Detavernier, C.; Comrie, C.M.; Temst, K.; Vantomme, A.
Abstract: The solid solubility of the isomorphous monosilicides during the silicide reaction of Ni-Pt, Ni-Pd and Pt-Pd alloys on Si(100) is comparatively studied in the full composition range. Our study reveals that PtSi and PdSi, exhibiting a minor lattice mismatch, directly form a solid solution. In contrast, for larger differences in lattice parameters such as is the case for NiSi-PtSi and NiSi-PdSi, the mutually soluble phases coexist, prior to the formation of a solid solution at increased temperatures. Hence, it appears that the direct formation of a ternary monosilicide solid solution is inherently related to the lattice mismatch of the binary monosilicides. This finding provides an explanation for important differences observed in the elemental redistribution between the three systems, considered to be very similar up to now. Moreover, the different formation of a solid solution results in a fundamentally different nucleation of PdSi: while Ni lowers the nucleation barrier by reducing the contribution of the interface energy, Pt strongly increases the entropy of mixing which triggers the formation of the Pd-monosilicide at surprisingly low temperatures. Our results show that the lattice mismatch is a crucial parameter and determines the phase formation sequence and elemental redistribution during the silicide reaction.